CAP superfamily proteins (VdPRYs) manipulate plant immunity and contribute to the virulence of Verticillium dahliae - Yan He; Jun Wang; Junjiao Li; Xiayu Wang; Xingyong Yang; Jieyin Chen; Dandan Zhang (Mycology)
CAP (cysteine-rich secretory proteins, antigen5, pathogenesis-related proteins) superfamily proteins are widely distributed, can be subdivided into 11 subfamilies, and form a unique branch in fungi, named PRY proteins. Verticillium dahliae is a soil-borne fungal pathogen of vascular plants that causes plant Verticillium wilt. However, the roles of CAP superfamily proteins in this fungus is unclear. Here, four CAP superfamily members with a conserved domain were identified in V. dahliae: VdPRY1, VdPRY2, VdPRY3, and VdPRY4. VdPRY1 and VdPRY3 were found to be key in suppressing plant immune responses. Moreover, these four members are highly expressed during early infection of cotton by V. dahliae. Deleting VdPRY1, VdPRY2, or VdPRY3 reduced the fungus’s ability to cause disease, but VdPRY4 deletion did not affect virulence. Deletion of any of four members did not impact fungal growth or carbon source use. Yeast two-hybrid experiments suggest that these proteins may function through interactions with each other. This investigation has, for the initial time, elucidated the pivotal roles of V. dahliae CAP superfamily proteins in inhibiting plant immunity and exerting virulence during interaction with the host plant.